SINERGI PEMERINTAH DAN PESANTREN DALAM MEWUJUDKAN SDM BERKARAKTER DAN KOMPETEN DI ERA SOCIETY 5.0 - Samsul Rizal; Moh Ali; Dewi Cahyani (STKIP Pesisir Selatan, 2025)
The development of human civilization is characterized by efforts to balance technological progress with fundamental human values. In this context, collaboration between the government and Islamic boarding schools (pesantren) is crucial for creating human resources (HR) who are not only intellectually superior but also possess strong moral and spiritual character. This study aims to examine the forms of collaboration between the government and Islamic boarding schools (pesantren) in developing HR capable of adapting to digital change, as well as examining the various challenges and opportunities that arise during the transition to Society 5.0. The research method used is a qualitative approach through library research, by reviewing various references such as books, scientific articles, policy reports, and relevant online sources. The research findings indicate that the government has a strategic role in formulating policies and providing competency improvement programs for Islamic boarding school HR. Meanwhile, Islamic boarding schools play a crucial role in shaping the character, work ethic, and spirituality of students.